ANALYSIS OF POC CONTENT OF HERMETIA ILLUCENS LARVAE FEEDED WITH PALM OIL MEAL - rano sipayung; Sari Anggraini; Eben Ezer Tamba; Theo Valent Josep Kevin Simamora (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2026)
Palm kernel meal (PKE) is a byproduct of Palm Kernel Oil (PKO) production that contains high levels of fiber and protein, making it potentially useful as feed for Black Soldier Fly (Hermetia illucens) larvae. BSF larvae are then processed into liquid organic fertilizer (POC) due to their high protein content. This study used a quantitative method with a descriptive comparative test approach to analyze the effect of two types of feed, namely fermented palm kernel meal (P1) and food waste (P2), on larval weight and the nutrient content of C-organic, N, P, K, and pH of POC after anaerobic decomposition for 40 days. The results showed that fermented palm kernel meal produced a higher larval weight, namely 9.90 kg, compared to food waste of 5.45 kg. However, POC from larvae with food waste feed had a higher nutrient content than POC from fermented palm kernel meal feed.